Retrospective analysis of acute appendicitis in COVID-19 pandemic – A clinical study of 100 cases (Panacea Journal of Medical Sciences, 2024)
Background: Acute appendicitis is a very common abdominal emergency condition. The incidence varies from 5.7 to57 patient /lakh population per year in the world wide survey. It is frequent in both sexes, But highest in children & adolescences. Presentation of this condition is some time so confusing that it should be distinguished from other acute abdominal conditions in proper time and appropriate measures should be taken to treat the patients to avoid unwanted complications, this complication is probably more complicated in COVID-19 pandemic period.Objective: This study is designed to compare acute appendicitis cases in relation to clinical features, gradation of disease & post operative complications before COVID-19 (June 2019-March 2020) and during COVID-19 pandemic period (April 2020-October 2021). METHOD-Cases of the study were divided into 2-groups.Group-A (65 cases) in pre- pandemic period and Group-B (35 cases) in pandemic period. The study is based on the clinico-radiological features, laboratories investigations and gradation of disease. Gradation: Grade-I (probably appendicitis), Grade-II (definite appendicitis), Grade-III (perforation of appendices), Grade-IV (appendicular abscess), Grade-V (complicated appendicitis/ appendicular lump).Result: Out of 100 enrolled cases 65 belongs to pre pandemic and 35 in pandemic period. It was found that increase in post-operative complications, were more in higher grade groups during pandemic periods.Conclusion: The COVID-19 pandemic has great impact on diagnosis, treatment and increased complications in post operative period of acute appendicitis, probably due to late presentation in emergency department. Pandemic directly or indirectly affect the outcome of a disease process and management.